MACHINE LEARNING APPLICATIONS IN AGRICULTURE 4.0 –A RENAISSANCE IN THE FIELD OF AGRICULTURE, IMPACT ON THE PRECISION AGRICULTURE AND REVOLUTION IN CROP MANAGEMENT (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The paper focuses on the growth of the  agricultural sector from the past to current  trends and its growth in smart farming. The  agriculture sector in India has successfully met  the production targets set by the government and  has also set new production records in almost all  commodities. The paper is a bibliometric analysis  of the systematic literature review of precision  agriculture, including technical terms like IoT,  precision agriculture, machine learning, artificial  intelligence, and traditional farming. The paper  discusses the various phases in the agricultural  management system, including advancements  from the past centuries to current trends.
Keywords: IoT; precision agriculture; machine learning; artificial intelligence; traditional farming; crop disease detection; weed detection; yield prediction; crop recognition; soil management